2012
DOI: 10.1371/journal.pone.0046882
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Climatic Anomalies and West Nile Virus Incidence in the Northern Great Plains of the United States

Abstract: The northern Great Plains (NGP) of the United States has been a hotspot of West Nile virus (WNV) incidence since 2002. Mosquito ecology and the transmission of vector-borne disease are influenced by multiple environmental factors, and climatic variability is an important driver of inter-annual variation in WNV transmission risk. This study applied multiple environmental predictors including land surface temperature (LST), the normalized difference vegetation index (NDVI) and actual evapotranspiration (ETa) der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 56 publications
(59 reference statements)
5
61
0
1
Order By: Relevance
“…Our study also demonstrates that remote sensing medium spatial resolution imagery as MODIS can provide relevant environmental indicators for studies on WNV risk, as it was also recently shown in Northern America [34]. This analysis should include high resolution geolocation of WND cases (i.e.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Our study also demonstrates that remote sensing medium spatial resolution imagery as MODIS can provide relevant environmental indicators for studies on WNV risk, as it was also recently shown in Northern America [34]. This analysis should include high resolution geolocation of WND cases (i.e.…”
Section: Resultssupporting
confidence: 65%
“…The two latter were derived from MODIS imagery. These three indices vary seasonally and inter-annually, and are hypothesized to influence mosquito population dynamics, and WNV transmission [31,34,42]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these are seasonal shifts in mosquito feeding preferences from amplifying bird hosts to humans after birds have migrated 42 or differences in land use that impact bird reservoir community composition or viral prevalence. [52][53][54][55] Enzootic transmission of the virus can be decreased if mosquitoes feed on low reservoir-competent avian hosts 56 or by herd immunity in the bird population. 57 Others have documented the impact of human behavior and interventions on WNV incidence patterns such as mosquito control, neglected swimming pools that provide mosquito breeding habitat, or having water-holding containers in the backyard.…”
Section: 48mentioning
confidence: 99%